Czerwiec 1956 wiosną 1981. Poznań 1956 (1981) Tadeusza Litowczenki i Mirosława Kwiecińskiego - Jazdon, Mikołaj (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The article presents the making of the first documentary film depicting the traumatic events of the anticommunist uprising in Poznań in June 1956 as well as the difficult fate of the documentary after it had been completed. Its authors, Tadeusz Litowczenko and Mirosław Kwieciński, composed their Poznań 1956 (1981) of two interwoven narrative lines. Archive photographs with off screen commentary make the first narrative line while cinema-verite-like interviews with the participants of historical events make the other. The film analysis is aimed to underline the formal means employed in the film to present the opposing sites of the conflict. It also focuses on the historical context from the times when film was being made in the so called ‘festival of Solidarity movement’ in the early 1980s.